Pelatihan Welding Pada Siswa Teknik Kendaraan Ringan Di SMK Ma’arif NU Bawang - Nurul Burhan; Fahmy Fatra; Toni Setiawan; Fathur Rahman (TEMATIK, 2026)
Welding is an art form that can be applied and applied in craft products. The objectives of this community service activity are 1) to provide students with knowledge about welding techniques, 2) to train students' skills in making standing flower pots. The method of implementing the activity is in the form of initial evaluation, demonstration, practice, and final evaluation. The results of the training activities can be concluded that. 1) students' knowledge regarding welding techniques can be concluded that the average before training is 54.75 and after training is 80.25. 2) students' skills are seen from the neatness of the welding and the completion of the standing flower pot product, of the 20 participants who took part, all of them were able to complete their tasks.